Pengembangan Multimedia Pembelajaran Berbasis Ispring Suite Pada Mata Kuliah Sejarah Sastra Arab - Nur Hanifatus Sholeha; Nurul Hidayah; Afif Kholisun Nashoih (Prodi Pendidikan Bahasa Arab, Universitas Muhammadiyah Tangerang, 2022)
Arabic historical literature is a course that study about the development of the arabic historical literature based on the period and philology. Arabic historical literature course in Arabic education major is new courses that caused lack of reference and literature which available and easy to access. Another problem was the low of student reading interest that caused information transfer process did not run maximum. The purpose of this research is to develop learning media based on iSpring Suites Aplication in Arabic Historical Literature Course and also to count media effectiveness to increase student grade. This research used Research and Development (R&D) method with 4D (Define, Design, Develop, Dessiminate) model design. Data collection techniques are done by distributing questionnaires, observations and tests. The result of media validation test showed around 83% from material expert, 84% from language expert and 90% from media expert. The average from the three expert about 89% and can be categorized as good and decent.